Community Safety Well-Being and Touristic Spots - Assis, Dineu (2022)
Assis, D., Castro Neto, M. D., & Motta, M. (2020). Community Safety Well-Being and Touristic Spots: A Model Proposal to Correlate Safe Places and Touristic Spots Based in Open Data. In 2020 4th International Conference on Smart Grid and Smart Cities (ICSGSC) (pp. 136-144). [9248556] (4th International Conference on Smart Grid and Smart Cities, ICSGSC 2020). Institute of Electrical and Electronics Engineers Inc.. https://doi.org/10.1109/ICSGSC50906.2020.9248556